Global estimate of gastric cancer in Helicobacter pylori–infected population: A systematic review and meta‐analysis - Pormohammad, Ali; Mohtavinejad, Naser; Gholizadeh, Pourya; Dabiri, Hossein; Salimi Chirani, Alireza; Hashemi, Ali; Nasiri, Mohammad Javad (Journal of cellular physiology, 2019)
There is information regarding the rates of gastric cancer (GC) in different populations and the important role of Helicobacter pylori in GC development; however, no comprehensive study has yet been performed to investigate the prevalence of GC in H. pylori–infected patients. PubMed, Embase, and Cochrane Library through January 1, 2000 were searched without language restrictions. Quality of included studies was assessed with a critical appraisal checklist recommended by the Joanna Briggs Institute. All of the analyses were conducted using Comprehensive Meta‐Analysis Software Version 2.0 and Stata 14.0. Forty‐four studies from 17 countries were included. The pooled frequency of GC was 17.4% (95% confidence interval: 16.4–18.5) in H. pylori–infected population. The frequency of GC among H. pylori–infected population varied markedly across countries. The highest rate of GC was observed in H. pylori–infected individuals from Asian countries. The frequency of GC was relatively high in H. pylori–infected population in the world. However, the eradication of H. pylori might be a promising strategy for GC prevention, especially in high‐risk populations such as Asian countries. The frequency of gastric cancer (GC) among H. pylori–infected population varied markedly across countries. The highest rate of GC was observed in H. pylori–infected individuals from Asian countries. The frequency of GC was relatively high in H. pylori–infected population in the world. However, the eradication of H. pylori might be a promising strategy for GC prevention, especially in high‐risk populations such as Asian countries.